2002
DOI: 10.1007/s004050100400
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sex-hormone-receptor expression in laryngeal carcinoma

Abstract: There are significant differences in how laryngeal cancer affects the two genders, with cases occuring predominantly in males. This has been speculated to result from the different susceptibilities of the tumor cells to steroid sex hormones. Since the sex hormone action is mediated by specific cellular receptors, several previous studies have analyzed the presence of these sex-hormone receptors. However, the data on the receptor status for androgen, estrogen and progesterone receptors in laryngeal carcinomas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
(56 reference statements)
2
17
0
1
Order By: Relevance
“…Estrogen receptors function as transcription factors and play a role in the progression of several human malignancies. Although the expression of steroid receptors was controversial in laryngeal carcinoma (27), our results confirmed recent data showing ER-ß expression in laryngeal cancer (28). Table I.…”
Section: Discussionsupporting
confidence: 91%
“…Estrogen receptors function as transcription factors and play a role in the progression of several human malignancies. Although the expression of steroid receptors was controversial in laryngeal carcinoma (27), our results confirmed recent data showing ER-ß expression in laryngeal cancer (28). Table I.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated that 23–79% of laryngeal cancer cases express ERs (16–18,24), concluding that positive ER expression is gender independent with a positive prognostic influence on survival. However, other authors have not been able to identify ER expression in laryngeal cancer (25,26), therefore laryngeal carcinogenesis may be a hormonally independant process. Non-identification of ER in epithelial components of the normal larynges and laryngeal carcinomas has been confirmed (27).…”
Section: Discussionmentioning
confidence: 96%
“…The presence of classical cytosolic ERs is controversial in laryngeal cancer [22, 13]. Despite this, laryngeal cancer cells display E 2 responsiveness, as E 2 was found to increase proliferation of laryngeal cancer cells [8], and a non-genomic mechanism was implicated [24].…”
Section: Introductionmentioning
confidence: 99%